2015
DOI: 10.12740/pp/26078
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life of patients with irritable bowel syndrome before and after education

Abstract: 1. Quality of life of patients with irritable bowel syndrome is substantially reduced in all the examined spheres. 2. Education of patients with IBS resulted in enhanced quality of life and reduced disease-related complaints. 3. Education of patients with IBS plays a significant role in the entire therapeutic process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 22 publications
0
5
0
1
Order By: Relevance
“…Education on the therapeutic intervention should be provided in an empathetic and warm manner, providing ample time for the family to ask questions and to create a supportive patient-health professional relationship (70). Studies have not only shown the importance of dietary education for patients with FGID but also how more knowledge in general about the disorder, including pharmacological and nutritional therapy and the importance of follow-up, can enhance patient's quality of life (71,72). Ostgaard et al showed that adult patients with IBS who received two sessions of dietary guidance compared to those who did not, continued to have a healthy diet, improved quality of life, and reduced symptoms even after two years (73).…”
Section: Description Of Professional Guidance During the Dietary Trea...mentioning
confidence: 99%
“…Education on the therapeutic intervention should be provided in an empathetic and warm manner, providing ample time for the family to ask questions and to create a supportive patient-health professional relationship (70). Studies have not only shown the importance of dietary education for patients with FGID but also how more knowledge in general about the disorder, including pharmacological and nutritional therapy and the importance of follow-up, can enhance patient's quality of life (71,72). Ostgaard et al showed that adult patients with IBS who received two sessions of dietary guidance compared to those who did not, continued to have a healthy diet, improved quality of life, and reduced symptoms even after two years (73).…”
Section: Description Of Professional Guidance During the Dietary Trea...mentioning
confidence: 99%
“…Management of IBS involves an integrated approach [53] and treatment options include establishment of an effective patient-provider relationship, education, reassurance, nutritional interventions, drug therapy and psychological therapy [8]. In fact, patients who received information about the course of the disease, disease-related diet and lifestyle, medications and check-ups had their quality of life improved [54].…”
Section: Managementmentioning
confidence: 99%
“…Diagnosing an FD overlap syndrome may also present an ideal opportunity to provide more complete patient education about visceral hypersensitivity. 24 Visceral sensory abnormalities are common in DGBI and may contribute to the challenge of identifying the origin of refractory abdominal symptoms for both patients and clinicians. 25 Patients with a DGBI in one GI anatomic region frequently have additional symptoms referable to other parts of the gut 26 suggesting that visceral hypersensitivity may not respect anatomic boundaries and DGBI of different GI regions may in fact be manifestations of the same underlying pathophysiology.…”
Section: Discussionmentioning
confidence: 99%